Uji Aktivitas Ektrak Daun Palado (Agave angustifolia) Sebagai Antioksidan - Nur, Kurniati; Diah, Anang Wahid M.; Nuryanti, Siti (Jurnal Akademika Kimia, 2016)
Study on the antioxidant activity test has been conducted using palado (agave angustifolia) leaves from Tondo, Central Sulawesi. Palado plant is one of the succulent plants that can grow to a large size, and it is possible to contain antioxidant compounds. This study was conducted by an experimental method using maceration extraction technique and 1,1-difenil-2-picrylhydrazyl (DPPH) as the free radicals source, and vitamin C as the positive control, whereas UV-Vis spectrophotometer as for determining wavelength (Î») of palado leaves extracts. Sample used as much as 5 grams palado leaves, and methanol as the solvent. Variation concentrations of palado leaves extract were 20, 40, 60, 80, 100, 120, and 140 ppm. The results showed that the IC50 value of palado leaves extract was 26.182 ppm. Palado leaves extract is classified as a very powerful antioxidant based on the IC50 value. The optimum percentage antioxidant activity of palado leaves extract in inhibiting free radicals was by 84.84%.